(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The central nervous system (CNS) possesses a delicate yet robust system for maintaining and restoring its structural and functional integrity. One of the most studied mechanisms of repair after injury is remyelination, a process that is fundamentally dependent on the differentiation of oligodendrocyte precursor cells (OPCs) into mature, myelinating oligodendrocytes. Understanding the cellular and molecular underpinnings of OPC differentiation and remyelination is crucial for the design of therapies to treat demyelinating diseases like multiple sclerosis and acute CNS traumas such as spinal cord injury or stroke.